Ethical Integrity and Regulatory Compliance in Sharia-Compliant Multi-Level Marketing - Taufiq, Akhmad; Wibowo, Satrio (Al Urwah : Sharia Economics Journal, 2025)
Sharia-compliant Multi-Level Marketing (MLM) has emerged as an ethical alternative to conventional MLM models, aiming to align business practices with Islamic economic principles. However, the stigma of money game schemes continues to undermine consumer trust. This study investigates how Sharia-compliant MLM differentiates itself from exploitative schemes through ethical frameworks, structural mechanisms, and regulatory compliance. A qualitative approach was employed, combining semi-structured interviews with regulators, practitioners, and consumers (n=18) and document analysis of fatwas, regulatory frameworks, and company reports. Thematic analysis revealed four key findings: (1) Sharia-compliant MLM is product-driven and structured to eliminate riba, gharar, and maysir; (2) consumer skepticism persists despite fatwa endorsements, highlighting the need for stronger consumer education; (3) regulatory oversight varies across jurisdictions, with Malaysia and Indonesia providing benchmarks through formal fatwas and supervisory frameworks; (4) digital innovations such as blockchain and ethical e-marketing offer transparency but require ethical guidance and regulatory alignment. This study contributes by integrating Islamic business ethics, legitimacy theory, and consumer trust theory to explain how Sharia-based MLM can enhance legitimacy. Practically, it offers policy recommendations for regulators and governance frameworks for industry practitioners.